Oral hygiene habits among students from the Pachacútec, Ventanilla, Callao - Madrid Chumacero, Marco Tulio (2010)
A survey was performed which objective was to evaluate the oral hygiene habits among students from the Educational Institution (IE) No. 5130 at Pachacútec, Ventanilla, El Callao. The entire population was taken (225 children) who were 6, 12 and 15 years old. The results showed that 21.3% and 46.7% of the children brush their teeth once a day and more than once a day, respectively; 10.7% of them never brushes their teeth and 20% practices it sometimes. 34.7% of them has visited the dentist in the last six months, while 9.3% did it between the last six months to a year, and 26.7% has never gone to the dentist. 18.7% has done fluoride mouthwashing during two or more years, 9.3% has done fluoride mouthwashing just during one year, and 72.0% has never done fluoride mouthwashing at the Educational Institution. It is concluded that the oral hygiene habits of the 6, 12 and 15-year-old students from the Educational Institution No. 5130 at Pachacútec show that there is a need to develop a sustained mouthwashing program and health education to improve oral hygiene habits increasing the tooth brushing frequency.